Pengaruh Profitabilitas, Leverage dan Market Value terhadap Harga Saham pada Perusahaan Industri Barang Konsumsi yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - Nanda Dwi Priliana; G. Anggana Lisiantara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Companies that are members of the Consumer Goods Industry have very high competition, so they must continue to improve their company performance to survive in the face of competition. These conditions can affect the movement of stock prices. The way to measure company performance is by looking at the financial statements and considering the ratios in them. So this research was conducted to find out whether there is an influence between the profitability ratios (ROA, ROE), leverage (DAR) and market value (EPS) partially or simultaneously on share prices in consumer goods industry companies listed on the IDX in 2019-2021. This study uses secondary data and quantitative methods purposive sampling as a data collection method. The total sample used after the outliers were 144 companies. Multiple linear regression analysis using the SPSS program was used as a technique to analyze the data. The conclusion of this study is Profitability (ROA, ROE), Leverage (DAR) and Market Value (EPS) simultaneously have a significant effect on stock prices. Profitability (ROA) partially has no effect on stock prices. Profitability (ROE) partially has a significant effect on stock prices. Leverage (DAR) partially has no effect on stock prices, and Market Value (EPS) has a significant effect on stock prices. Keywords: Profitability, Leverage, Market Value, Stock Price.